Endoparasit Pada Ikan Kakap Merah (Lutjanus sp.) di Pantai Kelan, Bali; Potensi Bersifat Zoonosis - Hartini, Sri; Damriyasa, I Made; Suryaningtyas, Endang Wulandari (Current Trends in Aquatic Science, 2019)
One of the factors that reduce fish production and population is disease. This study aims to determine the various types of zoonotic endoparasites, prevalence, intensity, abundance, diversity index, relationship of fish length-weight, relationship length with the intensity of parasites, and the relationship between weight and intensity of parasites. This research was conducted at Kelan Beach, Bali from December 2018 to April 2019. The research used a descriptive method using purposive sampling for data retrieval. Endoparasites were found in 9 types, namely Cucullanus sp. (3 ind), Anisakis sp. (7 ind), Lecithochirium sp. (1 ind), Hamacreadium lethrini (6 ind), Helicometra sp. (1 ind), Siphoderina sp (7 ind). Trypanorhyncha (32 ind), Tetraphylidea (4 ind), and Acanthocephalus sp. (1 ind). Organs infected by endoparasites were stomach (34%), liver (3%), and intestine (63%). The highest prevalence obtained was Trypanorhyncha (37.5%). The highest intensity obtained was Hamacreadium lethrini and Cucullanus sp. about 3 ind / fish. The highest abundance obtained was Trypanorhyncha (80%). The diversity index was 1,583. The length and weight relationship of Red Snapper ( Lutjanus sp.) shows isometric relationship after t-test. Long relationship with parasite intensity has a very low relationship with a velue (r) of 0,142. The relationship between weight and parasite intensity has a very low relationship with a velue (r) of 0,139. Based on 9 types of endoparasites found 1 type is zoonotic namely Anisakis sp. that cause Anisakiasis disease.